Pyoderma gangrenosum among children in Senegal: 6 cases - Boubacar Ahy Diatta; Fatou Fall Toumbou; Assane Diop, Saer Diadie; Maodo Ndiaye; Moussa Diallo; Suzanne Oumou Niang; Assane Kane; Mame Thierno Dieng (Our Dermatology Online, 2017)
The pyoderma gangrenosum (PG) is a chronic ulcerative neutrophilic dermatosis rare in children. It is often associated with chronic inflammatory bowel disease, some systemic diseases and leukemias. We report six cases in children. We collected six cases, the average age was 10 years (4-15 years), the sex ratio was 0.16 (5 boys and 1 girl). The ulcerated clinical form of PG was noted in all children. The topography was in the lower limbs in five cases and in the cephalic extremity in three cases. The mean duration of evolution was 2 years (15 days-7 years). PG was associated with ulcerative colitis in one case. Oral corticosteroids were administered in all cases at a dose of 0.5 to 1 mg/kg. The complete healing of the cutaneous lesions was obtained. Two children were lost to sight. Our study reports a male predominance of PG in children with ulcerative clinical form of the limb and association with ulcerative colitis. Corticosteroids appear to be efficient, but may be limited by their complications.